Analisis Prioritas Peningkatan Kualitas Kawasan Alun-Alun sebagai Ruang Terbuka Publik di Kecamatan Namlea - Wa Ode Sitti Jurianti Aswad; Izky Ayu Setyaningrum (Jurnal Peweka Tadulako, 2026)
This study aims to analyze the priority for improving the quality of the Namlea District square area as a public open space based on visitors’ perceptions. This research employed a quantitative descriptive approach. Data were collected through observation, documentation, and questionnaires distributed to visitors of the square area. The data were analyzed using Importance Performance Analysis (IPA) to compare the performance level and importance level of 15 public open space attributes. The results show that the conformity level between performance and importance reached 83.23%, with an average performance score of 3.34 and an average importance score of 4.01. The IPA Cartesian diagram identified six attributes as the main improvement priorities: facility completeness, facility condition, availability of sports areas, cleanliness facilities, architectural aesthetic elements, and spaces for informal sector activities. The study concludes that the Namlea District square has strong potential as a public open space due to its strategic location and multifunctional role. However, its quality still needs to be improved, particularly in facilities and area management, to create a more comfortable, active, inclusive, and sustainable public space.